48Ti(alfa,p gamma)51V : vlakstruktuur, vertakkingsverhoudings en vlakleeftydbepalings - Van Rooyen, D. M.(Daniel Michael) (Stellenbosch : Stellenbosch University, 2012)
In die titel is die 48 en die 51 in boskrif.